(3ecGJHI GdTjN CHj GdeYGdis - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje MOhO bGFe GdOjf cJHJ CWGd Gddg HbGA GdTjN GdNjQ hENhJg HMaX eSGYi GdOjf heYGdeg s
(3BNQgG (B:s
(3hjLH Cf jYQahfG ef efge Gdjhe Ydi GdSff Gdbhje hef efge eDKQ HMaX GdMceI JeJ hGdMeO dehdGfG hMOg hGdTcQ dbGFe GdReGf YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B109s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds